Internalisasi Nilai Tarekat pada Santri Dayah: Studi di Dayah Darul Aman Aceh Besar dan Dayah Budi Mesja Lamno Jaya - Asmanidar, Asmanidar; Fazal, Khairil (Sociology Department Of Syiah Kuala University, 2023)
This article aims to describe the internalization of tarekat values among students in Dayah Darul Aman Aceh Besar and Dayah Budi Mesja Lamno Aceh Jaya. The data sources for this study include the leaders and elements of both institutions, as well as the students who reside in them. Data collection was conducted through observation, interviews, and literature review. The study reveals that students in Dayah Darul Aman Aceh Besar and Dayah Budi Mesja Lamno Aceh Jaya apply the teachings of Tarekat Naqsyabandiyah in their religious practices. They engage in activities such as baiat (initiation), khataman/khususiyah (recitation of the entire Quran), manaqiban (poetic eulogies), general religious gatherings, haul akbar (commemoration of spiritual leaders), uzlah (spiritual retreat), and rabithoh (spiritual connection) with both the mursyid (spiritual guide) of the tarekat and fellow followers. They also perform zikir jahr (loud remembrance of God) and zikir sirri (silent remembrance of God). These teachings play a significant role in their daily lives, helping to enhance their religious understanding and transform individual behavior, particularly in terms of religious social conduct. The changes in religious social behavior among the students of both institutions encompass several aspects. Firstly, they are inclined to help others. Secondly, there is an increase in fostering social ties. Thirdly, there is heightened awareness of promoting good deeds and preventing wrongdoing.AbstrakArtikel ini bertujuan untuk menggambarkan tentang internalisasi nilai tarekat pada santri di Dayah Darul Aman Aceh Besar dan Dayah Budi Mesja Lamno Aceh Jaya. Sumber data kajian ini meliputi Pimpinan dan unsur-unsur kedua dayah tersebut, serta para santri yang mondok di kedua dayah. Pengumpulan data dilakukan melalui observasi, wawancara, dan kepustakaan. Kajian ini menunjukkan bahwa Santri Dayah Darul Aman Aceh Besar dan Dayah Budi Mesja Lamno Aceh Jaya menerapkan konsep ajaran Tarekat Naqsyabandiyah dalam praktik keagamaan mereka. Mereka melakukan baiat (ijazah), khataman/khususiyah, manaqiban, pengajian umum, haul akbar, uzlah, rabithoh (hubungan), baik dengan mursyid tarekat maupun sesama pengikut tarekat. Mereka juga melaksanakan zikir jahr maupun zikir sirri. Ajaran-ajaran ini menjadi bagian penting dalam kehidupan sehari-hari, membantu meningkatkan pemahaman keagamaan dan mengubah perilaku individu, terutama perilaku sosial keagamaan. Perubahan perilaku sosial keagamaan yang terjadi pada santri kedua dayah tersebut meliputi beberapa hal. Pertama, mereka cenderung suka menolong; kedua, terjadi peningkatan dalam menjalin silaturahmi; ketiga, kesadaran terhadap amar makruf nahi mungkar.